PENERAPAN MODEL PROBLEM POSING BERSETTING COOPERATIF TIPE THINK PAIR SHARE PADA TOPIK ASAM BASA UNTUK MENINGKATKAN PENGUASAAN KONSEP MAHASISWA - Rasmawan, Rahmat (Universitas Tanjungpura, 2010)
The low student understanding of concepts on the topic due to lack of acid base interaction with the material studied. This study aims to determine the conception of students, student influence and respond to the model after learning problems set Posing think pair share. The sample in this study is the students who attend a course basic chemistry II 2008/2009 school year in chemical education courses totaling UNTAN FKIP 23 people with a form of research design quasy experiment. Data collection techniques used is about the shape of the test and questionnaire response essays. The results showed that there are significant differences abilities before learning concepts with students after learning. The amount of influence of 7.49 with a very high category. Conceptions of students in accordance with the concept of the experts increased by 52.9%. Students respond positively to the learning model of cooperative problem set type possing think pair share.Kata Kunci: Asam basa, Problem Posing, Kooperatif, Think Pair Share.